2019
DOI: 10.1093/cercor/bhz091
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Watershed Model of Fluid Intelligence in Childhood and Adolescence

Abstract: Fluid intelligence is the capacity to solve novel problems in the absence of task-specific knowledge and is highly predictive of outcomes like educational attainment and psychopathology. Here, we modeled the neurocognitive architecture of fluid intelligence in two cohorts: the Centre for Attention, Leaning and Memory sample (CALM) (N = 551, aged 5–17 years) and the Enhanced Nathan Kline Institute—Rockland Sample (NKI-RS) (N = 335, aged 6–17 years). We used multivariate structural equation modeling to test a pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…These properties positively affect processing speed and functional connectivity within and between brain regions (Ferrer et al, 2013; Kievit et al, 2016; Penke et al, 2012; Wendelken et al, 2017). Moreover, greater white-matter-tract integrity has been repeatedly associated with greater mental abilities in different age groups (Booth et al, 2013; Ferrer et al, 2013; Fuhrmann, Simpson-Kent, Bathelt, the CALM Team, & Kievit, 2020; Kievit et al, 2016; Wendelken et al, 2017).…”
Section: Why Do Benefits In the Speed Of Higher-order Processing Givementioning
confidence: 99%
“…These properties positively affect processing speed and functional connectivity within and between brain regions (Ferrer et al, 2013; Kievit et al, 2016; Penke et al, 2012; Wendelken et al, 2017). Moreover, greater white-matter-tract integrity has been repeatedly associated with greater mental abilities in different age groups (Booth et al, 2013; Ferrer et al, 2013; Fuhrmann, Simpson-Kent, Bathelt, the CALM Team, & Kievit, 2020; Kievit et al, 2016; Wendelken et al, 2017).…”
Section: Why Do Benefits In the Speed Of Higher-order Processing Givementioning
confidence: 99%
“…For example, machine learning methods have distinguished subgroups of the children in the cohort with distinct individual profiles of cognition, learning and behaviour (Astle, Bathelt, CALM Team, & Holmes, 2019;Bathelt et al, 2018), and network analysis has identified inter-related behavioural and cognitive symptoms that are not captured by traditional diagnostic criteria (Mareva & Holmes, 2019). Using structural equation modelling, work has examined a priori distinctions between fluid and crystallized abilities (Simpson-Kent et al, 2020) and evaluated conceptually distinct models of hierarchical, cognitive-only factors (Fuhrmann, Simpson-Kent, Bathelt, & Kievit, 2019). These findings have yet to be integrated in a single, multi-level model of learning difficulties.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…It also may lead to missing many meaningful relationships latent in the experimental data which have become big data nowadays. Another effort is to compare cognitive concepts (or psychological constructs) with each other by trying to identify relationships in idiosyncratic features or performances in several cognitive tasks (Beaty et al, 2014;Chuderski and Jastrzêbski, 2018;Eisenberg et al, 2019;Fuhrmann et al, 2019;Rey-Mermet et al, 2019) as well as by investigating overlaps in neural substrates using neuroimaging and neuropsychological methods (Hassabis et al, 2007;Mullally and Maguire, 2014;Woolgar et al, 2018;Brandl et al, 2019;Jonikaitis and Moore, 2019). While these approaches provide insights based on empirical facts, completing such low-profile tasks exhaustively is challenging.…”
Section: Introductionmentioning
confidence: 99%